Modified Autonomous Key Management Scheme with Reduced Communication/Computation Costs in MANET - Lin, Chu-Hsing; Lee, Chen-Yu; Chen, Deng-Jyi (Computing and Informatics, 2012)
The growing applications of mobile ad hoc networks (MANETs) have made related security issues much more important. B. Zhu et al. proposed a key management scheme using Shamir's secret sharing scheme to construct an Autonomous Key Management (AKM) hierarchy structure. However, Shamir's secret sharing in AKM to control key hierarchy incurs high message transmission costs. This paper modifies the secret sharing scheme and applies it to AKM to reduce communication and computation costs.